Reconstructing atrocity prevention / edited by Sheri P. Rosenberg, Cardozo Law School, Tiberiu Galis, Auschwitz Institute, New York, Alex Zucker, Independent Scholar. - Rosenberg, Sheri P.; Galis, Tiberiu; Zucker, Alex (Cambridge University Press, 2016)
In the two-and-a-half decades since the end of the Cold War, policy makers have become acutely aware of the extent to which the world today faces mass atrocities. In an effort to prevent the death, destruction and global chaos wrought by these crimes, the agendas for both national and international policy have grown beyond conflict prevention to encompass atrocity prevention, protection of civilians, transitional justice and the responsibility to protect. Yet, to date, there has been no attempt to address the topic of the prevention of mass atrocities from the theoretical, policy and practicing standpoints simultaneously. This volume is designed to fill that gap, clarifying and solidifying the present understanding of atrocity prevention. It will serve as an authoritative work on the state of the field.